Floral biology and pollination strategy of Durio (Malvaceae) in Sarawak, Malaysian Borneo - WIN SENG NG; JAYASILAN MOHD-AZLAN; SIN YENG WONG (Society for Indonesian Biodiversity, 2020)
Abstract. Ng WS, Mohd-Azlan J, Wong SY. 2020. Floral biology and pollination strategy of Durio (Malvaceae) in Sarawak, Malaysian Borneo. Biodiversitas 21: 5579-5594. This study was carried out to investigate on the flowering mechanisms of four Durio species in Sarawak. The anthesis started in the afternoon (D. graveolens and D. zibethinus), evening (D. kutejensis) or midnight (D. griffithii); and lasted between 11.5 hours (D. griffithii) to 20 hours (D. graveolens). All four Durio species are generalists. Individuals of a fruit bat (Eonycteris spelaea, Pteropodidae) are considered as the main pollinator for D. graveolens, D. kutejensis, and D. zibethinus while spiderhunter (Arachnothera, Nectariniidae) is also proposed as a primary pollinator for D. kutejensis. Five invertebrate taxa were observed as secondary or inadvertent pollinators of Durio spp.: honeybee, Apis sp. (Apidae), stingless bee, Tetrigona sp. (Apidae), nocturnal wasp, Provespa sp. (Vespidae), pollen beetle (Nitidulidae), and thrip (Thysanoptera). Honey bees and stingless bees pollinated all four Durio species. Pollen beetles were found to pollinate D. griffithii and D. graveolens while nocturnal wasps were found to pollinate D. kutejensis and D. zibethinus. Thrips were found to pollinate D. griffithii only. Floral rewards include nectar, pollen and staminodes. The nectar production of D. graveolens, D. kutejensis, and D. zibethinus increased from the start of anthesis until just after midnight but decreased from then onwards. Durio griffithii produced consistent nectar concentration with inconsistent volume. Durio graveolens, D. griffithii, and D. zibethinus are partially self-incompatible.